THE EFFECT OF USING RIDDLE TECHNIQUE ON STUDENTS’ VOCABULARY MASTERY OF THE 2017/2018 TENTH GRADE STUDENTS OF SMK SWASTA PEMDA LANGKAT BAHOROK - Lusiana Eka Rahmadanta Sitepu (Universitas Islam Negeri Sumatera Utara Medan, 2018)
Learning mthod innovation will influence learning media used and it is hoped to improve learning qualities. This study was intended to find out The Effect of Using Riddle Technique on Students’ Vocabulary Mastery of The 2017/2018 Tenth Grade Students of Smk Swasta Pemda Langkat Bahorok Kabupaten Langkat. There were two classes for the population with the total 56 students. And for the sample, all population were taken out. The data were collected by administering tests. The data was applied statistically. Then the data were analyzed by applying the calculation of test. Havinf the data been computed by using t-test formula, it shows that tobserved in certain degree of freedom 28 and 0.05, is higher than ttable. And the value is 9.83 > 2.048. in other words, the hypothesis “there is any Effect of Using Riddle Technique on Students’ Vocabulary Mastery of The 2017/2018 Tenth Grade Students of Smk Swasta Pemda Langkat Bahorok Kabupaten Langkat, is accepted. Learning method with interactive technique can improve students’ vocabulary, because if the method can interest students’ attention they will enjoy and easy to receive the lesson.